H2A.Z/H2B.Z double‐variant nucleosomes inhabit the AT‐rich promoter regions of the Plasmodium falciparum genome. Issue 5 (28th January 2013) - Hoeijmakers, Wieteke A. M.; Salcedo‐Amaya, Adriana M.; Smits, Arne H.; Françoijs, Kees‐Jan; Treeck, Moritz; Gilberger, Tim‐Wolf; Stunnenberg, Hendrik G.; Bártfai, Richárd
Summary Histone variants are key components of the epigenetic code and evolved to perform specific functions in transcriptional regulation, DNA repair, chromosome segregation and other fundamental processes. Although variants for histone H2A and H3 are found throughout the eukaryotic kingdom, variants of histone H2B and H4 are rarely encountered. H2B.Z is one of those rare H2B variants and is apicomplexan‐specific. Here we show that in Plasmodium falciparum H2B.Z localizes to euchromatic intergenic regions throughout intraerythrocytic development and together with H2A.Z forms a double‐variant nucleosome subtype. These nucleosomes are enriched in promoters over 3′ intergenic regions and their occupancy generally correlates with the strength of the promoter, but not with its temporal activity. Remarkably, H2B.Z occupancy levels exhibit a clear correlation with the base‐composition of the underlying DNA, raising the intriguing possibility that the extreme AT content of the intergenic regions within the Plasmodium genome might be instructive for histone variant deposition. In summary, our data show that the H2A.Z/H2B.Z double‐variant nucleosome demarcates putative regulatory regions of the P. falciparum epigenome and likely provides a scaffold for dynamic regulation of gene expression in this deadly human pathogen.